Rapid onset of mafic magmatism facilitated by volcanic edifice collapse. Issue 12 (17th June 2015) - Cassidy, M.; Watt, S. F. L.; Talling, P. J.; Palmer, M. R.; Edmonds, M.; Jutzeler, M.; Wall‐Palmer, D.; Manga, M.; Coussens, M.; Gernon, T.; Taylor, R. N.; Michalik, A.; et al.
Abstract Volcanic edifice collapses generate some of Earth's largest landslides. How such unloading affects the magma storage systems is important for both hazard assessment and for determining long‐term controls on volcano growth and decay. Here we present a detailed stratigraphic and petrological analyses of volcanic landslide and eruption deposits offshore Montserrat, in a subduction zone setting, sampled during Integrated Ocean Drilling Program Expedition 340. A large (6–10 km3) collapse of the Soufrière Hills Volcano at 130 ka was followed by explosive basaltic volcanism and the formation of a new basaltic volcanic center, the South Soufrière Hills, estimated to have initiated <100 years after collapse. This basaltic volcanism was a sharp departure from the andesitic volcanism that characterized Soufrière Hills' activity before the collapse. Mineral‐melt thermobarometry demonstrates that the basaltic magma's transit through the crust was rapid and from midcrustal depths. We suggest that this rapid ascent was promoted by unloading following collapse.